Misoprostol and teratogenesis in neonates - Scabora da Silva, Mariana Beatriz [UNESP]; Ferreira, Aline de Assis [UNESP]; Habr, Soraya Ferreira [UNESP]; Bernardi, Maria Martha [UNESP] (Univ Sao Paulo, Conjunto Quimicas, 2009)
This paper is focused in some aspects of maternal exposure to misoprostol during perinatal period, and the abortive and teratogenesis effects on the fetus. The causes of malformations were revised, taking into account chemical, physical and environmental factors as well as the interaction between them. There are evidences that the practice of abortion tripled in Southern and Northeaster Brazil in 15 years, and one of the most frequent forms of abortion is through the use of misoprostol. In Brazil, 1991, 288,700 women were hospitalized as a consequence of complications induced by abortion attempt with this medicine. This fact resulted in the ban of misoprostol across our country, by Decree 344/98 determined by the Health Ministry. The use of misoprostol requires special control and it is allowed only in hospitals, with supervision of the municipal health surveillance. Among the more severe problems affecting the non-aborted child is the injury on the central nervous system, which frequently results in the Moebius syndrome. This is a congenital and non-progressive paralysis of the VI and VII cramal nerves, frequently bilateral, which produces a unexpressive facial appearance and convergent Strabismus. Even banned in our country, abortion is illegally practiced, being deprived of proper knowledge about misoprostol teratogenic effects on the fetus as well as the risks involving mothers.
Keywords: Perinatal toxicology; Misoprostol Malformations; Moebius syndrome; Abortion Cytotee